Measurement placement for power system state estimation using decomposition technique - Chawasak Rakpenthai (2018)
This paper applies the concept of distributed processing to the problem of measurement placement for power system state estimation. The proposed method uses the minimum condition number of the measurement matrix as a criterion in conjunction with sequential elimination to reach the near optimal placement positions. Firstly, the entire network of the power system is decomposed into smaller sub-networks. Then, in each sub-network, the optimal positions for measurement placement are determined by using the minimum condition number criteria. A heuristic algorithm for reducing the number of placement sites is also presented in order to minimize the communication costs. The numerical experimental results on the IEEE 14, 30, and 118 bus systems indicate that the proposed technique will provide a measurement matrix with smaller condition number and the computation time is much shorter than the non-decomposition approach. © 2005 Elsevier B.V. All rights reserved.